Experimental and numerical investigations on large‐section rectangular CFT columns with distributive beam under axial compression. (30th September 2022) - Guo, Xiaonong; Zhang, Chaozhong; Luo, Jinhui; Zhang, Yuanzhi; Chen, Shaozhen; Gao, Shuyu
Summary: In order to improve the co‐working performance between the core concrete and steel tube for large‐section rectangular concrete‐filled steel tubular (LSCFT) columns when a vertical load is directly applied to the steel tube, a distributive beam is proposed as a load transferring measure. Four scaled LSCFT column specimens with different details were tested under axial compression to investigate the mechanical behavior and load transferring mechanism of the LSCFT columns with a distributive beam. The experimental results indicated that the bearing capacity of the LSCFT columns without a distributive beam was close to the yield capacity of the steel tube and the load shared by the core concrete was negligible. In contrast, the specimen with a distributive beam and inner stiffeners could bear a much higher load. In addition, refined nonlinear finite element models were developed to further analyze the load‐transferring mechanism of LSCFT columns with different details. The numerical results showed that the ultimate load of the specimen with a distributive beam and inner stiffeners was much closer to the theoretical value calculated from Chinese code CECS159:2004. Setting a distributive beam and inner stiffeners simultaneously in LSCFT columns could ensure the cooperation between the core concrete and steel tube.